(untitled) (Pedagogical Horizons, 2024)
At the University College of Teacher Education Tyrol, the location-related needs of schools are managed using the STEPS concept. This concept enables processes to be structured, the needs of all stakeholders to be coordinated in the best possible way and the impact of teacher training to be increased. The five-stage STEPS concept corresponds to the impact objectives and management processes of the pedagogy package and supports the participatory development of locations at various levels of action. Based on a classic PDCA cycle, school locations are provided with information and tools for the sustainable planning and implementation of further training events for location development on the website of the University College of Teacher Education Tyrol. The attractiveness and effectiveness of school site-related teacher training was examined as part of a research project at the University College of Teacher Education, and the results are presented and discussed. The effectiveness was examined on the basis of evaluation data and as part of a research project. The results were analyzed on several levels and correlations were presented.